Orthogeriatric Service Reduces Mortality in Patients With Hip Fracture. (June 2016) - Stenqvist, Charlotte; Madsen, Christian Medom; Riis, Troels; Jørgensen, Henrik Løvendahl; Duus, Benn Rønnow; Lauritzen, Jes Bruun; van der Mark, Susanne
Introduction: Orthogeriatric service has been shown to improve outcomes in patients with hip fracture. The purpose of this study is to evaluate the effect of orthogeriatrics at Bispebjerg University Hospital, Denmark. The primary outcome is mortality inhospital and after 1, 3, and 12 months for patients with hip fracture. The secondary outcome is mortality for home dwellers and nursing home inhabitants. Materials and Methods: This is a retrospective clinical cohort study with an historic control group including all patients with hip fracture admitted from 2007 to 2011. Patients with hip fracture are registered in a local database, and data are retrieved retrospectively using the Danish Civil Registration Number. Results: We included 993 patients in the intervention group and 989 patients in the control group. A univariate analysis showed only significantly decreased mortality inhospital 6.3% vs 3.1% ( P = .009) after orthogeriatrics. However, when adjusting for age, gender, and American Society of Anaesthesiologists (ASA) score in a multivariate analysis, including all patients with hip fracture, we find significantly reduced mortality inhospital (odds ratio [OR] 0.35), after 30 [OR 0.66] and 90 days [OR 0.72] and 1 year [OR 0.79]). When using a univariate analysis for home-dwelling patients, we found significantly reduced mortality inhospital (8.3-2.0%, P < .0001), after 30 days (12.2-6.8%, P = .004) and 90 days (20.5-13.0%, P = .002). One-year mortality was not significant. Patients from nursing homes had no significant decreasing mortality at any point of time in the univariate analysis. Conclusion: We have shown significant decreases for inhospital, 30 day, 90 day, and 1-year mortality after implementation of orthogeriatric service at Bispebjerg Hospital when adjusting for age, gender, and ASA score. Future trials should include frail patients with other fracture types who can benefit from orthogeriatrics.